2021
DOI: 10.3390/v13060964
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Investigating the Dynamics of Pigeon Circovirus Recombination in Domesticated Pigeons Housed in a Single Loft

Abstract: Pigeon circovirus (PiCV) infects pigeon populations worldwide and has been associated with immunosuppression in younger pigeons. Recombination is a common mechanism of evolution that has previously been shown in various members of the Circoviridae family, including PiCV. In this study, three groups of pigeons acquired from separate lofts were screened for PiCV, and their genome sequence was determined. Following this, they were housed in a single loft for 22 days, during which blood and cloacal swab samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 40 publications
5
13
0
Order By: Relevance
“…The high intensity of recombination may suggest that frequent co-infections of different PiCV strains. Moreover, recently, Khalifeh A. et al has demonstrated that recombination plays a role in PiCV evolution through animal experiment [ 58 ]. Thus, the recombination seemed to be a key mechanism for PiCV evolution [ 21 , 23 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high intensity of recombination may suggest that frequent co-infections of different PiCV strains. Moreover, recently, Khalifeh A. et al has demonstrated that recombination plays a role in PiCV evolution through animal experiment [ 58 ]. Thus, the recombination seemed to be a key mechanism for PiCV evolution [ 21 , 23 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rep is considered to be essential for viral replication and plays a crucial role in cellular immunity [6,42]. Recombination events are also widely found in other viruses, such as porcine circovirus, canine circovirus, pigeon circovirus, duck circovirus and goose circovirus [41,[43][44][45][46]. The hotspot of recombination events is Rep, but it is still relatively conserved in ssDNA viruses, indicating that recombination may have little influence on the diversification of Rep.…”
Section: Discussionmentioning
confidence: 99%
“…Within the first decade after the short report of Schmidt [ 1 ], retrieved records showed detection of the virus in several other countries including Northern Ireland [ 16 , 34 , 69 , 70 ], Germany [ 15 , 44 ], Italy [ 31 , 71 ], France [ 72 ], Belgium [ 30 , 33 , 34 ], and Japan [ 21 , 38 ]. Meanwhile, between 2003 and 2012, researchers in Czech Republic [ 29 , 32 ], Poland [ 36 , 58 , 67 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ], Denmark [ 30 ], Slovenia [ 81 , 82 ], Hungary [ 66 , 83 ], United Arab Emirates [ 84 ], Libya [ 85 ], Nigeria [ 83 , 86 ], and Taiwan [ 59 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ] reported first local detections of PiCV. Lastly, during the most recent decade of PiCV research, new publications and reports were also produced from Brazil [ 40 ], Iran [ 94 , 95 ], Iraq […”
Section: Picv Knowledge—current Understanding and Updatesmentioning
confidence: 99%
“…More recently, wider interest and more studies focused on the role of recombination as an evolutionary driver of circovirus evolution have been published [ 40 , 66 , 73 , 76 , 102 ]. Besides the observed frequent mutations in the cp gene, this observed high genetic diversity in PiCV sequences is also attributed as a product of constant recombination driving the evolution of this virus [ 75 , 88 ].…”
Section: Picv Knowledge—current Understanding and Updatesmentioning
confidence: 99%
See 1 more Smart Citation